Further Delineation of the TRAPPC6B Disorder: Report on a New Family and Review - Nair, Pratibha; El-Bazzal, Lara; Mansour, Hicham; Sabbagh, Sandra; Al-Ali, Mahmoud Taleb; Gambarini, Alicia; Delague, Valerie; El-Hayek, Stephany; Mégarbané, André (Journal of Pediatric Genetics, 2019)
Pathogenic variants in the TRAPPC6B gene were recently found to be associated in three consanguineous families, with microcephaly, epilepsy, and brain malformations. Here, we report on a 3.5-year-old boy, born to consanguineous Lebanese parents, who presented with developmental delay, lactic acidosis, postnatal microcephaly, and abnormal brain magnetic resonance imaging. By whole exome sequencing, a novel homozygous likely pathogenic variant in exon 1 of the TRAPPC6B gene (c.23T > A; [p.Leu8*]) was identified. A review of the clinical description and literature is discussed, pointing out the phenotypic heterogeneity associated with mutations in this gene.
Keywords: Lebanon; whole exome sequencing; TRAPPC6B